Dora the Explorer. Dora saves Fairytale Land [videorecording (DVD)] - Ptacek, Fátima; Gursory, Koda; Cruz, Victor (Dora the Explorer., 2015)
Fairytale Land is in trouble, and only magic water from Sparkling Lake can save it! Help Dora and Boots journey deep into the Never-to-be-Seen-Again Forest to bring magic back to Fairytale Land!